2022
DOI: 10.1038/s41598-022-20412-3
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of oregano (Origanum vulgare) versus silymarin in experimentally induced hepatic encephalopathy

Abstract: Hepatic encephalopathy (HE) is a deterioration of brain function in patients suffering from chronic liver disease, cirrhosis as a result of elevated blood ammonia and the production of pseudo-neurotransmitters. Herein, we investigated the chemical composition of hexane extract from Origanum vulgare (O. vulgare) leaves as well as its possible protective effects against thioacetamide (TAA)-induced HE in rats. GC–MS analysis of the extract revealed tentative identification of twenty-five compounds (82.93%), predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…[44] Further, six flavonoids were isolated from the 80 % aqueous methanol extract of P. racemosa J.W. Moore leaves and identified as avicularin (19), quercetin 3-O-β-D-arabinopyranoside (20), quercetin 3-O-β-Dglucopyranoside (16), quercitrin (17), cynaroside (21), and quercetin (22). P. psuedocaryophyllus exhibits strong antioxidant ability due to a content of polyphenols (199.33 � 3.79 mg/g) & flavonoids (28.32 � 1.46 mg/g) such as rutin (23) which can be obtained from the ethanol extract.…”
Section: Flavonoidsmentioning
confidence: 99%
“…[44] Further, six flavonoids were isolated from the 80 % aqueous methanol extract of P. racemosa J.W. Moore leaves and identified as avicularin (19), quercetin 3-O-β-D-arabinopyranoside (20), quercetin 3-O-β-Dglucopyranoside (16), quercitrin (17), cynaroside (21), and quercetin (22). P. psuedocaryophyllus exhibits strong antioxidant ability due to a content of polyphenols (199.33 � 3.79 mg/g) & flavonoids (28.32 � 1.46 mg/g) such as rutin (23) which can be obtained from the ethanol extract.…”
Section: Flavonoidsmentioning
confidence: 99%
“…[24][25][26] Therefore, the protective effects of natural antioxidants are currently drawing considerable attention in disease prevention. [17,[27][28][29] Different natural plant extracts and oils such as Moringa oleifera, Syzygium aromaticum and Rosmarinus officinalis showed hepatoprotective properties against carbon tetrachloride (CCl 4 ) and diclofenac sodium -induced liver injuries in rats. [30][31][32] Afghan ash is the trivial name of Fraxinus xanthoxyloides which belongs to Oleaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports revealed that flavonoids can suppress transcription factors imperative for regulatory mediators involved in inflammation [24–26] . Therefore, the protective effects of natural antioxidants are currently drawing considerable attention in disease prevention [17,27–29] . Different natural plant extracts and oils such as Moringa oleifera , Syzygium aromaticum and Rosmarinus officinalis showed hepatoprotective properties against carbon tetrachloride (CCl 4 ) and diclofenac sodium ‐induced liver injuries in rats [30–32] …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] These studies have led to the development of plant-based medications. [20][21][22][23] In recent years, the use of phytochemicals derived from dietary components or traditional medicines to combat or prevent human diseases has received considerable public and scientific interest. [24][25][26][27][28] Natural compounds have demonstrated promising effects in the treatment of different kinds of cancer during the current stage of medication development.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of medicinal plants in healthcare dates back to ancient times, and different studies have been carried out worldwide to validate their efficacy [17–19] . These studies have led to the development of plant‐based medications [20–23] . In recent years, the use of phytochemicals derived from dietary components or traditional medicines to combat or prevent human diseases has received considerable public and scientific interest [24–28] .…”
Section: Introductionmentioning
confidence: 99%